IDENTIFICATION OF CRYPTOSPORIDIUM SP. IN SUMATRAN ORANGUTAN AND BORNEAN ORANGUTAN AT NORTH SUMATERA WILDLIFE PARK - Pohan, Indah Serly; Hanafiah, Muhammad -; Rahmi, Erdiansyah; Winaruddin, Winaruddin; Rosmaidar, Rosmaidar (Buletin Veteriner Udayana, 2023)
Cryptosporidium sp. is a zoonotic intestinal protozoa in orangutans which is transmitted through contaminated water (waterborne disease). This study aims to determine Cryptosporidium sp. which infects the sumatran orangutan ( Pongo abelii ) and the bornean orangutan ( Pongo pygmaeus ) in North Sumatera Wildlife Park. The samples used were 3 orangutan fecal samples from different locations, two bornean orangutans in Medan Wildlife Park and one sumatran orangutan in Pematang Siantar Animal Park. Samples were examined using the floatation method and the modified Ziehl-Neelsen method. The results showed that from 3 samples of orangutan feces (sumatran and bornean orangutan), 2 positive tails from bornean orangutans were found containing Cryptosporidium oocysts, namely the C. parvum species. In this study, it can be concluded that the orangutans in Medan Wildlife Park, the bornean orangutan were infected with cryptosporidiosis.